Introduction - Ben Zvi, Ehud (The journal of Hebrew scriptures, 2007)
This conversation with John Barton, Oracles of God: Perceptions of Prophecy in Israel after the Exile (London: Darton, Longman and Todd, 1986) began in a special session of the research program “Israel and the Production and Reception of Authoritative Books in the Persian and Hellenistic Periods” that was held at the annual meeting of the European Association of Biblical Studies (Vienna, 2007). It includes an introduction by the editor and contributions by Philip R. Davies, James Kugel, Hindy Najman and a response by John Barton.